PENGARUH GOOD CORPORATE GOVERNANCE PADA KINERJA LEMBAGA PERKREDITAN DESA DENPASAR DENGAN KOMITMEN ORGANISASI SEBAGAI PEMODERASI - Sidney, Gusti Ayu; Ratna Sari, Maria M. (E-Jurnal Akuntansi; Vol 16 No 2 (2016), 2016)
This study was conducted to determine the effect on the performance of good corporate governance of LPD in Denpasar as well as good corporate governance determine the effect on the performance of LPD in Denpasar moderated by organizational commitment. Performance in this study was measured by balance scorecard. This research was conducted at 35 LPD in Denpasar. Data used in this study are primary data and secondary data. The samples used are 35 by saturated sampling technique. The data analysis technique used in this study are Moderated Regression Analysis (MRA). Results from this study stated that (1) good corporate governance positively affects the performance of LPD in Denpasar and (2) commitment to the organization is not able to moderate the influence of good corporate governance on the performance of LPD in Denpasar.
Keywords: LPD Performance, Balance Scorecard, Good Corporate Governance and Organizational Commitment.